Get Your Paws off of My Pixels: Personal Identity and Avatars as Self - Graber, Mark Alan; Graber, Abraham David (JMIR Publications, 2010)
There is an astounding silence in the peer-reviewed literature regarding what rights a person ought to expect to retain when being represented by an avatar rather than a biological body. Before one can have meaningful ethical discussions about informed consent in virtual worlds, avatar bodily integrity, and so on, the status of avatars vis-à-vis the self must first be decided. We argue that as another manifestation of the individual, an individual's avatar should have rights analogous to those of a biological body. Our strategy will be to show that (1) possessing a physical body is not a necessary condition for possessing rights; (2) rights are already extended to representations of a person to which no biological consciousness is attached; and (3) when imbued with intentionality, some prostheses become "self." We will then argue that avatars meet all of the conditions necessary to be protected by rights similar to those enjoyed by a biological body. The structure of our argument will take the form of a conditional. We will argue that if a user considers an avatar an extension of the self, then the avatar has rights analogous to the rights of the user. Finally, we will discuss and resolve some of the objections to our position including conflicts that may arise when more than one individual considers an avatar to be part of the self.